2004
DOI: 10.1017/s0003581500045807
|View full text |Cite
|
Sign up to set email alerts
|

The Winchester Hoard: A Find of Unique Iron Age Gold Jewellery from Southern England

Abstract: An unusual group of gold jewellery was discovered by a metal detectorist near Winchester in southern England in 2000. The hoard included two possibly unique massive necklaces made in a clearly classical style, but different from typical classical necklaces and from the torcs and collars of Iron Age Europe. The hoard also contained extremely rare gold versions of types of brooches commonly made in bronze and iron in north-west Europe during the first century BC, the end of the pre-Roman Iron Age. This paper des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…There is good reason to suppose that the owners of such good quality jewellery and awards as those in the hoard would have possessed other equally valuable but more bulky items, not only more cash but also table wares, perhaps including high-quality metal pieces such as the silver cups from Hockwold, Norfolk. 104 Even if the veteran and his household had had the time to hide other possessions in various locations within the building, perhaps grouped by type, effectively forming a hoard which had been dispersed by the depositor(s) rather than by later activity, the rarity of coin hoards and precious metal items in Colchester's Boudican destruction levels implies that only the small and 100 The two matching but differently-sized sets of Iron Age gold jewellery forming the Winchester hoard were interpreted as either for female and male, or senior and junior, individuals: Hill et al 2004, 3, fig. 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is good reason to suppose that the owners of such good quality jewellery and awards as those in the hoard would have possessed other equally valuable but more bulky items, not only more cash but also table wares, perhaps including high-quality metal pieces such as the silver cups from Hockwold, Norfolk. 104 Even if the veteran and his household had had the time to hide other possessions in various locations within the building, perhaps grouped by type, effectively forming a hoard which had been dispersed by the depositor(s) rather than by later activity, the rarity of coin hoards and precious metal items in Colchester's Boudican destruction levels implies that only the small and 100 The two matching but differently-sized sets of Iron Age gold jewellery forming the Winchester hoard were interpreted as either for female and male, or senior and junior, individuals: Hill et al 2004, 3, fig. 14.…”
Section: Resultsmentioning
confidence: 99%
“… 100 The two matching but differently-sized sets of Iron Age gold jewellery forming the Winchester hoard were interpreted as either for female and male, or senior and junior, individuals: Hill et al 2004, 3, fig. 14. …”
mentioning
confidence: 99%
“…It may be speculated whether this crisis represents comparable power shifts to those of 1st century BC mainland Britain which have been attributed to interactions with the Roman world. While, of course, purely internal dynamics may also lie at the heart of this development, the Broighter hoard with its Roman or Mediterranean-made chain neck ornaments (Evans 1897, 391-408;Raftery 1984, 181-92) recalls the Winchester, Hampshire hoard (Hill et al 2004) that has been suggested to be a diplomatic gift with which external parties tried to exert influence in local politics. The emergence of the new societal structures hypothesised here during a time of crisis after the collapse of Late Bronze Age society structures is also implied in the small dataset and may give us an insight into how societal reorganisation was achieved in this power vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…The workmanship and high refined gold content of the Winchester torcs, which were deposited on a hilltop in Hampshire, suggest a Mediterranean origin (Hill et al . 2004; La Niece et al . 2018), and Creighton (2006, 44) argues that these may have been imperial gifts ‘entirely appropriate to a returning British prince..., representing both northern European symbolism and Roman power and technology.’ Whether these objects arrived in Britain as sought‐after trade goods or one‐off diplomatic gifts, they likely fitted into a wider prestige exchange system involving the circulation of precious metals.…”
Section: Silver As a Medium Of Mediation: The Biography Of The Hallatmentioning
confidence: 99%